PENGEMBANGAN MODEL PROBLEM BASED LEARNING BERBASIS STRATEGI SCAFFOLDING PADA PEMBELAJARAN MENENTUKAN IDE POKOK - Isti Nur Hayanah; Ghaida Nisa; Sylvia Ervina Safitri; Shabrina Caesharah Aulia; Wiwi Isnaeni; Ellianawati Ellianawati (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2019)
ABSTRACT This study aims to improve the ability of students to determine the main ideas through the Problem Based Learning model with scaffolding strategies. The subjects of this study were the fifth grade students of Sidomulyo 04 Elementary School, which amounted to 39 students, Gedanganak State Elementary School 03 which amounted to 31 students, and Kalirejo 02 Elementary School totaling 30 students. Data collection uses the method of observation, interviews, questionnaires, documentation and tests. The data analysis technique used is descriptive. The results of the study can be concluded that the application of the Problem Based Learning model based on the scaffolding strategy improves the ability to determine the main idea in the fifth grade elementary school students of Class R.A. Kartini Semarang Regency.Keywords: Problem Based Learning; Scaffolding Strategy ABSTRAKPenelitian ini bertujuan untuk meningkatkan kemampuan siswa dalam menentukan ide pokok melalui model Problem Based Learning dengan strategi scaffolding. Subjek penelitian ini adalah siswa kelas V SD Negeri Sidomulyo 04 yang berjumlah 39 siswa, SD Negeri Gedanganak 03 yang berjumlah 31 siswa, dan SD Negeri Kalirejo 02 yang berjumlah 30 siswa. Pengumpulan data menggunakan metode observasi, wawancara, angket, dokumentasi dan tes. Teknik analisis data yang digunakan adalah deskriptif. Hasil penelitian dapat disimpulkan bahwa penerapan model Problem Based Learning berbasis strategi scaffolding meningkatkan kemampuan menentukan ide pokok pada siswa kelas V SD Gugus R.A. Kartini Kabupaten Semarang.         Kata Kunci: Problem Based Learning; Strategi Scaffolding